If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + -7 = 3x + 65 Reorder the terms: -7 + 9x = 3x + 65 Reorder the terms: -7 + 9x = 65 + 3x Solving -7 + 9x = 65 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -7 + 9x + -3x = 65 + 3x + -3x Combine like terms: 9x + -3x = 6x -7 + 6x = 65 + 3x + -3x Combine like terms: 3x + -3x = 0 -7 + 6x = 65 + 0 -7 + 6x = 65 Add '7' to each side of the equation. -7 + 7 + 6x = 65 + 7 Combine like terms: -7 + 7 = 0 0 + 6x = 65 + 7 6x = 65 + 7 Combine like terms: 65 + 7 = 72 6x = 72 Divide each side by '6'. x = 12 Simplifying x = 12
| s^2-7s+14=-20 | | b(5b^2+34b^1)=0 | | y+12=8 | | 1.7(2x+5)=3(x-8.1) | | 2k(3k-2)-5(3k-2)= | | 21x^2-22x-24=0 | | 3(8w-2)=46-2(12w+1) | | (15-4x)-(20-2x)= | | 2x^2=12x-9 | | 2y^2+y=6 | | 12+5a=-13 | | (x+4)(X+3)= | | 7x+12=5x-4 | | -4x^2+19x-21=0 | | 240=x^2+22x | | 5(x-2)= | | (2a-5)-(3a+1)= | | 2(3w+2)-12=3w-11 | | 6r+2=56 | | 2x+x+x=180 | | 3(w-6)-5w=-36 | | h=-5t^2+60t | | 7x+3x+90=180 | | -16t^2+24t+3=12 | | X^3-9x^2+20x-12=0 | | 3x(x-9)= | | 3+2t=13 | | 5x-2= | | 3x^3+3x^2-11x-10=0 | | 4.2(x-1)=9.8 | | (x)(x)(x)+4(x)(x)-25x-100=0 | | 25x-10= |